Isolation of Methicillin Resistant - Staphylococcus aureus in Midwifery Students Faculty of Medicine Universitas Padjadjaran SeptemberâDecember 2012 - Panirchelvam, Robinee; Megantara, Imam; Sudiro, Melati (Althea Medical Journal, 2015)
Background: Methicillin Resistant-Staphylococcus aureus (MRSA) is resistant bacteria to certain types ofÂ beta-lactam antibiotics. Commonly, the MRSA infection is acquired in hospitals, long-term care facilities,Â or similar institutional settings. Mid-wives are one of the health professional that have a major risk to getÂ MRSA infection and could lead the infection among patients. This research is aimed to identify MRSA amongÂ the midwifery studentsMethods: A descriptive study was conducted from SeptemberâDecember 2012 at the MicrobiologyÂ laboratory to identify the proportion of MRSA among the mid-wife students from Faculty of Medicine,Â Universitas Padjadjaran. Twenty-five samples were chosen using simple random sampling based on theirÂ registration number. The inclusion criterias were healthy students, and 18 to 22 years old. Both nostrilsÂ were sampled with a sterile culture swab on both the subjectâs nostrils. Gram staining was done in order toÂ identify the gram positive bacteria, Staphylococcus aureus. The samples were inaculated in Mannitol saltÂ agar (MSA), incubated for 24 hours and at 37 Ì C. After 24 hours, catalase and coagulase tests were done.Â Moreover, for the susceptibility testing, the chosen media for this study was Mueller Hinton Agar (MHA)Â and with 30Î¼g Cefoxitin disk. After incubation, the zone of inhibition of the colony less than â¤ 21mm wasÂ considered resistant to methicillin.Results: Colonization of MRSA was about 3 out from 25 samplesConclusions: The MRSA colonization in the anterior nasal does exist in midwife students, a further studyÂ with more samples should be conducted. [AMJ.2015;2(1):204â7]